Semiclassical estimate of the Coulomb excitation of the giant dipole resonance in Pb208 - Galetti, D. [UNESP]; Eiras, A. [UNESP]; De Souza Cruz, F. F.; Marinelli, J. R.; De Moraes, M. M.W. (American Physical Society (APS), 1993)
A semiclassical approach to study pure Coulomb excitation of Pb208 giant dipole isovector resonance is examined. We consider medium energy projectiles and assume the target excitation to be described by a simple Goldhaber-Teller model. It is shown that the main features concerning the angular distribution are obtained in the angular range described by the model and an estimate is made of the pure Coulomb dipole contribution to the measured cross sections. © 1993 The American Physical Society.